Do Firms Knowingly Sell Overvalued Equity? - Lee, Inmoo (Journal of Finance, 1997)
This article examines the relationship between top executives' trading and the long-run stock returns of seasoned equity issuing firms. Primary issuers, who sell mostly newly issued primary shares, significantly underperform their benchmarks, regardless of the top executives' prior trading pattern. However, top executives' trading is reliably associated with the stock returns of secondary issuers, who sell mostly secondary shares previously held by existing shareholders. On average, secondary issuers do not underperform their benchmarks. The results suggest that increased free cash flow problems after issue play an important role in explaining the underperformance of issuing firms.